Analysis of Adipokines and some Steroid Hormones in Myocardial Infarction (Baghdad Science Journal, 2023)
The most common cause of death is cardiovascular disease (CVD), with ischemic heart disease being the most notable type. There is a propensity to raise the sensitivity of methods in contemporary laboratory for diagnosing of CVD, and assessing key as CVD bio-indicators. The urgent task is to seek for different indicators as a hopeful tool for early detection and monitoring of myocardial infarction in blood samples only. This study comprised 117 Volunteers, recorded with both genders in the age range of 32-64 years old. The volunteers were categorized into two groups: 67patients of myocardial infarction, other group embraced 50 healthy individuals. The samples of blood were collected and directed for biochemical analysis to evaluate estradiol, testosterone, progesterone, adiponectin, leptin, and lipid profile [total cholesterol, triglycerides, high density lipoprotein (HDL), and low-density lipoprotein (LDL)] levels in each group. The following conclusion can be drawn from this study based on statistical assessment of bio-indicator parameters, significantly reduced of testosterone and HDL (P <0.001) levels in myocardial infarction, within non-significantly elevated P <0.061 of progesterone levels in myocardial infarction patients as compared with healthy individuals. The remaining biochemical tests indicated significantly elevated levels in patients with myocardial infarction such as estradiol (P <0.001), adiponectin (P <0.001), leptin (P <0.001), total cholesterol (P <0.001), triglycerides (P <0.001) and LDL (P <0.001) levels. Adipokines (adiponectin, leptin) and some steroid hormones (estradiol, testosterone) show crucial roles in the improvement of metabolic and cardiovascular diseases and may be utilized as bio-pointer for myocardial infarction exposure, medical conduct and severity. This acknowledgment offers early diagnosis of disease and progression.